If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -10) * 10 = 60 Reorder the terms: (-10 + n) * 10 = 60 Reorder the terms for easier multiplication: 10(-10 + n) = 60 (-10 * 10 + n * 10) = 60 (-100 + 10n) = 60 Solving -100 + 10n = 60 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '100' to each side of the equation. -100 + 100 + 10n = 60 + 100 Combine like terms: -100 + 100 = 0 0 + 10n = 60 + 100 10n = 60 + 100 Combine like terms: 60 + 100 = 160 10n = 160 Divide each side by '10'. n = 16 Simplifying n = 16
| -18x^2+61x+7=0 | | y/4=-92 | | 2(3x-4)+2=12 | | 9x+18=18x+4 | | 8y=25.6 | | d+6+2x=-3 | | -4x-3+9x+5=-6-8x+20+10x | | 8=8p+13-13p | | 4x-50=62 | | ((x-118.75)/118,75)*100-4=0 | | 8y=2.56 | | 27=6+c | | 5x-7+3x=2x+5 | | 7.68=3w | | 15+11=26 | | X/3-6=14 | | 6/3+3/7 | | P-2=-1/2 | | (2g^2+3x)dx+2+gdy=0 | | 4x+20=4(x-5) | | 3.2=u | | 4v=5.12 | | (9x+5)(2x^2-5x-3)=0 | | 3(-2-4x)=2(2+b) | | 2x-3+6x-8=4+2x | | -3y+7x=15 | | (2g^2+3x)dx+2xgdy=0 | | 3/6+3/7 | | 5/x+6=10 | | -6+b=-18 | | 3x+2(7x-11)=131 | | 3(-16+4x)=-24 |